ANALISIS DETERMINAN WANITA PEKERJA SEKSUAL DENGAN KEJADIAN INFEKSI MENULAR SEKSUAL - Yulica Aridawarni (Jurnal Obstretika Scientia, 2014)
The purpose of this study to obtain information about the relationship between age, education, length of service and number of customers being the incident sexually transmitted infections in the region of the Puskesmas Bakauheni South Lampung in Year 2012. This research is a descriptive analytic cross sectional approach. The population in this study was a WPS direct and indirect health centers that are in the territory of South Lampung regency Bakauheni as many as 169 people. Sampling was conducted with a total of 154 sampling as much greater risk of having sexually transmitted infection is the number of customers, the old work. Lower risk for experiencing sexually transmitted infections is age. The same risk of experiencing sexually transmitted infections is education.